PENGOLAHAN BAMBU MENJADI ANYAMAN DALAM MENINGKATKAN KECAKAPAN HIDUP BAGI ANGGOTA KELOMPOK ECOVILAGE ANNADOPAH - Anggriani, Mita; Iqva, Valdio; Anjani Puteri, Widhi; Karwati, Lilis; Hamdan, Ahmad (Jurnal Pengabdian Masyarakat Indonesia, 2023)
The problem found was the lack of productivity carried out regularly by the group for processing bambu into woven material to improve life skills for members of the Annadopah ecovillage group and the abilities they possessed were not very advanced. This research used a qualitative descriptive type of research. This research is to provide a comprehensive picture regarding a problem or creative idea to be used as an innovative solution. The data used in this research is related to ideas related to community empowerment programs, and this research uses primary data which refers to data that continues to develop according to problems in the field. To help their welfare, the Annadopah group succeeded in selling ebeg woven products to consumers, namely to cracker factories. and to improve the skills of Annadopah group members by carrying out besek training to become more skilled. so that the welfare of members of the annadopah group can improve, the annadopah group must be more routine in chicken farming to increase its productivity, so that the welfare of the family or group can further increase or remain stable.